1991
DOI: 10.1104/pp.96.3.962
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Chloroplast Differentiation in Soybean Cells in Suspension Culture

Abstract: Suspension cultures of SB-P cells of soybean (Glycine max) provide a novel, reproducible, and readily manipulable greening system useful for inducing chloroplast differentiation. The cells are subcultured and grown heterotrophically (3% sucrose)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
(35 reference statements)
0
6
1
Order By: Relevance
“…1e,f), which is different from the report of enlarged nucleoli found in var2 white cells18. Overall, chloroplasts found in VMW are closer in appearance to those observed in photoautotrophic hairy root suspension cultures3132 which are capable of producing secondary metabolites33.…”
Section: Resultsmentioning
confidence: 67%
“…1e,f), which is different from the report of enlarged nucleoli found in var2 white cells18. Overall, chloroplasts found in VMW are closer in appearance to those observed in photoautotrophic hairy root suspension cultures3132 which are capable of producing secondary metabolites33.…”
Section: Resultsmentioning
confidence: 67%
“…Questions thus arise regarding the pathways of (x-amylase translocation in the cultured cells. Amyloplasts have been considered as nonphotosynthetic chloroplasts because both organelles originate from proplastids and appear to be interconvertible (Gillott et al, 1991). Translocation of proteins to chloroplasts and extracellular compartments via different pathways is generally accepted (Vemer and Schatz, 1988).…”
Section: A-amylases May Be Translocated Via Unidentified Pathwaysmentioning
confidence: 99%
“…During the 10 min 12CO2 chase period, the proportion of label in malate continued to rise somewhat while that in citrate declined slowly. Although we and others (Gillot et al 1991) have shown the presence of starch grains in the chloroplasts of SB-P cells, there is little or no starch metabolism occurring in SB-P cells (Martin et al 1984;Horn et al 1992). Labeled citrate is probably formed from a relatively small amount of labeled malate which enters the citric acid cycle and is converted to citrate.…”
Section: Discussionmentioning
confidence: 55%